Knowledge and Practice of Fertility Behavior among the Musahar Women in Nepal - KC, Ganga (Patan Pragya, 2020)
Musahars are the Terai Dalit community living in low land; basically Southern part of Nepal and the most deprived and marginalized groups. The aim of this study is to identify the nexus between knowledge, practices and its relation to fertility behavior and adoption of family planning methods. Fertility is a way through which human beings biologically substitute themselves in order to continue their existence on earth. This study reveals that married women and those who have children had relatively better knowledge about fertility behavior and methods of family planning than newly married and unmarried females. Similarly, adolescent mothers consistently had low level of use in each of the contraceptive methods mentioned by the respondents during the study. In addition, the study shows that many of older mothers enjoyed more support from their husbands compared to adolescent mothers when it comes to decision on whether fertility related issues and use method of family planning. This information suggests that interpersonal communication between husbands and wives on the use of contraceptive was relatively higher among older mothers compared with adolescent mothers. There is a huge impact of explanatory variables of the research topic like age, ethnicity, education, marital status, employment status, knowledge of family planning, number of children and attitude on the use of modern contraceptives etc. to the use of contraceptives.